ANALISIS RASIO KEUANGAN DAERAH DI KABUPATEN/KOTA PROVINSI SULAWESI TENGGARA - Satrio, Dimas Fajar; Digdowiseiso, Kumba (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. This study tries to analyze the financial performance of regional governments after fiscal decentralization by analyzing the financial ratios in the regional budget realization reports for 17 districts / cities in Southeast Sulawesi for the 2015-2018 period. The measurement results show that the ratio of fiscal decentralization is still very low below 20%, financial dependence on the central government is also very high followed by ineffective PAD management. The findings indicate that in general the existence of fiscal decentralization does not encourage regional independence, especially in districts / cities in Southeast Sulawesi.